Short oligonucleotides as external guide sequences for site-specific cleavage of RNA molecules with human RNase P. - Werner, M (1998)
Human RNase P recognizes a small model substrate consisting of only the 5' leader sequence, aminoacyl acceptor stem, and T stem and loop of a tRNA precursor. It was demonstrated here that a bimolecular construct in which the T loop is opened between G57 and A58 (tRNA numbering system) is still processed by RNase P. The strand that is cleaved can be considered the target RNA, whereas the other strand serves as an external guide sequence (EGS). The nucleotides corresponding to nt 58-60 in the T loop could be deleted without affecting cleavage of the substrate. Thus, the complete T loop can be replaced by the single-stranded sequence UUCG or UUCA (nt 55-57 in the T loop). The four nucleotides UUCR possibly form a structure that resembles the uridine turn in the T loop of tRNA. Because recognition by RNase P is independent of the helical sequence, this motif can be used for targeting RNA molecules for EGS-directed cleavage by human RNase P. Chemically modified EGSs with 2'-O-methyl groups also showed activity in inducing RNase P cleavage. Several 13-mer EGSs targeted to the 2.1-kb surface antigen mRNA of hepatitis B virus (HBV) were designed and tested using a co-transcriptional cleavage assay with a 2.1-kb HBV transcript. Some of the new EGSs were capable of inducing cleavage of the HBV RNA by RNase P.